The ion channel Trpc6a regulates the cardiomyocyte regenerative response to mechanical stretch - Rolland, Laura; Abaroa, Jourdano Mancilla; Faucherre, Adèle; Drouard, Aurélien; Jopling, Chris (Frontiers in Cardiovascular Medicine, 2024)
Myocardial damage caused, for example, by cardiac ischemia leads to ventricular volume overload resulting in increased stretch of the remaining myocardium. In adult mammals, these changes trigger an adaptive cardiomyocyte hypertrophic response which, if the damage is extensive, will ultimately lead to pathological hypertrophy and heart failure. Conversely, in response to extensive myocardial damage, cardiomyocytes in the adult zebrafish heart and neonatal mice proliferate and completely regenerate the damaged myocardium. We therefore hypothesized that in adult zebrafish, changes in mechanical loading due to myocardial damage may act as a trigger to induce cardiac regeneration. Based on this notion we sought to identify mechanosensors which could be involved in detecting changes in mechanical loading and triggering regeneration. Here we show using a combination of knockout animals, RNAseq and in vitro assays that the mechanosensitive ion channel Trpc6a is required by cardiomyocytes for successful cardiac regeneration in adult zebrafish. Furthermore, using a cyclic cell stretch assay, we have determined that Trpc6a induces the expression of components of the AP1 transcription complex in response to mechanical stretch. Our data highlights how changes in mechanical forces due to myocardial damage can be detected by mechanosensors which in turn can trigger cardiac regeneration.